2020
DOI: 10.32734/jst.v3i2.3967
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Content Test on Sliced Papaya in Area of Universitas Sumatera Utara

Abstract: Papaya is a fruit that is often consumed in Indonesia and has increased consumption from 2015-2016 based on SUSENAS 2016. Papaya has high water content (85-90%) and the pH is near neutral. This makes papaya vulnerable and suitable medium for the growth of pathogenic microbes. The presence of pathogenic microbes in papaya can cause health problems for those who consumed them. Objectives this study was to observe the microbial content of sliced papaya in the Universitas Sumatera Utara. Method this research was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results of the raw material analysis showed that the jicama puree had a moisture content of 80.52%, while the pineapple puree of 89.09%. The results of this study followed Lubis [9] regarding the manufacture of papaya fruit puree with pineapple puree with moisture content ranging from 13.10 to 15.47%. The more the amount of pineapple puree, the moisture content of the fruit leather produced increases.…”
Section: Chemical Analysis Of Fruit Leathermentioning
confidence: 79%
See 1 more Smart Citation
“…The results of the raw material analysis showed that the jicama puree had a moisture content of 80.52%, while the pineapple puree of 89.09%. The results of this study followed Lubis [9] regarding the manufacture of papaya fruit puree with pineapple puree with moisture content ranging from 13.10 to 15.47%. The more the amount of pineapple puree, the moisture content of the fruit leather produced increases.…”
Section: Chemical Analysis Of Fruit Leathermentioning
confidence: 79%
“…A hundred grams of the puree mixture was poured into nonstick aluminum pans with a 6-by-6-cm surface and a thickness of 2-3 mm, and dried for about 8 hours at 60 o C in the oven. The method and base formulation developed by Kwartiningsih and Mulyanti serves as the basis for making fruit leather [9].…”
Section: The Production Of Fruit Leathermentioning
confidence: 99%
“…In children, sepsis caused 26%–50% of all AKI compared to 7%–10% of AKI caused by primary renal diseases ( 17 ). The incidence of AKI in septic patients admitted to the intensive care unit (ICU) ranges from 13% to 78%, depending on the severity of sepsis and the AKI criteria ( 18 ). AKI can be caused by a variety of factors, including sepsis, age, and primary disease ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a life-threatening organ dysfunction caused by dysregulation of the immune system against infection. Evidence of infection was obtained from physical examination, radiological examination, laboratory examination, and blood culture ( 18 ). Because of the high incidence of AKI due to sepsis, the difficulty in making a diagnosis, and the poor impact that arises from late diagnosis, it is essential to conduct a study to determine the role of urinary KIM-1, IL-18, and IGFBP-7 biomarkers in predicting the AKI occurrence in children with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The 90% sewage sludge and 10% rejected papaya binder reached a moisture content of 31%. The high-water content of papaya, approximately 85-90% [31], affected the moisture content of the final product of briquettes.…”
Section: Effect Of Binder Type and Composition On Moisture Content Of...mentioning
confidence: 99%